Genome-wide identification of the OVATE gene family of proteins in soybean and expression profiling under salt stress - Zhan, Fan; Wang, Yi; Zhang, Lili; Yu, Yuehua; Ni, Zhiyong (Frontiers in Plant Science, 2025)
OVATE family proteins (OFPs), a class of plant-specific transcription factors, have been increasingly demonstrated to play pivotal roles in multiple aspects of plant growth and development. However, their functional characterization in soybean (Glycine max) remains largely unexplored. In this study, we conducted a genome-wide identification of OFP genes in soybean, followed by comprehensive analyses, including phylogenetic reconstruction, gene structure characterization, conserved motif and sequence alignment assessments, chromosomal localization, collinearity evaluation, promoter cis-acting element profiling, transcriptome-based expression pattern investigation, and quantitative polymerase chain reaction validation. Key findings revealed that the soybean genome harbors 42 GmOFP genes, all of which contain the conserved OVATE domain and are distributed unevenly across 19 chromosomes. Most members of this gene family exhibit single-exon architectures, with conserved motif analysis demonstrating that Motif 1 and Motif 2 collectively constitute the OVATE domain. Collinearity analysis indicated that a majority of GmOFPs underwent duplication events during evolution. Promoter analysis revealed abundant cis-regulatory elements associated with abiotic stress responses, hormonal regulation, light responsiveness, and growth-related processes. Expression profiling revealed that GmOFP genes exhibit tissue-specific expression patterns across various soybean organs, with several GmOFP genes showing differential responsiveness to salt stress. These findings provide crucial insights into the molecular characteristics and potential biological functions of GmOFPs, establishing a theoretical foundation for further investigations into their regulatory mechanisms in soybean growth, development, and stress adaptation.